2001
DOI: 10.2527/2001.7992397x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gestation feeding strategy on body composition of gilts at farrowing and response to dietary protein in a modified lactation.

Abstract: Previous experiments have indicated that reproductive function in lean, modern genotypes may be more dependent on body protein mass than, as previously believed, on body lipid reserves. This was investigated in a 3 x 2 factorial arrangement of treatments, involving 60 first-parity sows, comparing three pregnancy feeding strategies and two lactation diets. During pregnancy, sows were fed either a basal diet (5 g lysine/kg, 13 MJ of DE/kg [C]) or the same quantity of basal diet + energy source [E], or additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
13
0
4
Order By: Relevance
“…Foram utilizados 14 artigos distribuídos nos continentes europeu e americano, publicados de 2000 a 2006 em revistas indexadas internacionais (PRUNIER et al, 2001, SINCLAIR et al, 2001COOPER et al, 2001a, CLOWES et al, 2003MAES et al, 2004;RAMANAU et al, 2004;VAN DER PEET-SCHWERING et al, 2004;YOUNG et al, 2004;RENSIS et al, 2005;YOUNG et al, 2005b;LANDBLOM et al, 2006) e nacionais (GUEDES & NOGUEIRA, 2000;HASHIMOTO et al, 2004;LIMA et al, 2006). As informações relevantes das seções de material e métodos e resultados de cada artigo foram inseridas numa base de dados elaborada em planilha Excel.…”
Section: Methodsunclassified
“…Foram utilizados 14 artigos distribuídos nos continentes europeu e americano, publicados de 2000 a 2006 em revistas indexadas internacionais (PRUNIER et al, 2001, SINCLAIR et al, 2001COOPER et al, 2001a, CLOWES et al, 2003MAES et al, 2004;RAMANAU et al, 2004;VAN DER PEET-SCHWERING et al, 2004;YOUNG et al, 2004;RENSIS et al, 2005;YOUNG et al, 2005b;LANDBLOM et al, 2006) e nacionais (GUEDES & NOGUEIRA, 2000;HASHIMOTO et al, 2004;LIMA et al, 2006). As informações relevantes das seções de material e métodos e resultados de cada artigo foram inseridas numa base de dados elaborada em planilha Excel.…”
Section: Methodsunclassified
“…O conteúdo de gordura e proteína no leite é influenciado pela dieta lactacional; logo, níveis elevados de proteína na dieta resultam em maior percentagem de gordura e proteína no leite (SINCLAIR et al, 2001).…”
Section: Resultsunclassified
“…Foram utilizados 14 artigos publicados de 2000 a 2006, em revistas indexadas internacionais (PRUNIER et al, 2001;SINCLAIR et al, 2001;COOPER et al, 2001;CLOWES et al, 2003a;MAES et al, 2004;RAMANAU et al, 2004; VAN DER PEET-SCHWERING et al, 2004;YOUNG et al, 2004;RENSIS et al, 2005;YOUNG et al, 2005b;LANDBLOM et al, 2006) e nacionais (GUEDES & NOGUEIRA, 2000;HASHIMOTO et al, 2004;LIMA et al, 2006). As tabelas do NRC (1998) e de ROSTAGNO et al (2000) foram avaliadas juntamente com os resultados da metanálise.…”
Section: Methodsunclassified
“…However, long-term effects on the progeny, i.e., whether the differences at weaning were still evident at market weight and/or whether they affected carcass and pork quality, were not investigated in their study. Sinclair et al (2001), on the other hand, showed no significant effect of energy or protein intake during pregnancy on piglet growth. This difference between experiments may be due to the lower nutritional drain in lactation of the sows in the experiment of Sinclair et al (2001), so any effects of the gestational feeding strategy were masked.…”
mentioning
confidence: 97%
“…Sinclair et al (2001), on the other hand, showed no significant effect of energy or protein intake during pregnancy on piglet growth. This difference between experiments may be due to the lower nutritional drain in lactation of the sows in the experiment of Sinclair et al (2001), so any effects of the gestational feeding strategy were masked. In the experiment of Sinclair et al (2001), gilts were fed more total lysine (31 or 47 g d -1 vs. 6 to 30 g d -1 ) in lactation, but their litters grew more slowly (about 1.6 vs. 2.0 kg d -1 ) than those in the experiment of Kusina et al (1999).…”
mentioning
confidence: 97%